The ballerina mindset : how to protect your mental health while striving for excellence - Fairchild, Megan (Life, 2021)
"Learn how to thrive in intense, competitive environments with these secrets from one of America's premiere ballerinas--and get a sneak peek at what her life is really like. Ballet may look glamorous and effortless to audience members, but it requires grueling discipline. It's a competitive and physically and mentally demanding career that combines elite athleticism, artistry, and performance. Not only do dancers rehearse for six to eight hours a day before performing at night, but they also must make it all look easy! As a principal ballerina with New York City Ballet and a one-time Broadway star--not to mention a mother of three and an MBA student--Megan Fairchild is all too familiar with these challenges. In The Ballerina Mindset, she shares all the wisdom she's learned from her nearly two-decade career, drawing upon her own experiences to show us how she learned to overcome challenges ranging from stage fright to negative feedback to a packed calendar to weight management--and how we can do the same. Inspiring, warm, and revelatory, The Ballerina Mindset is the perfect how-to guide for dancers, athletes, artists, and anyone struggling to stay sane in a high-pressure environment"--